Platelet volume indices for the prognosis of acute ischemic stroke patients with intravenous thrombolysis. (3rd April 2019) - Xie, Dewei; Xiang, Weiwei; Weng, Yiyun; Li, Jia; Xu, Ling; Zhang, Xu; Chen, Zhibo
Abstract: Objective: We aimed to investigate whether platelet volume indices (PVIs) were associated with an unfavorable clinical outcome in acute ischemic stroke (AIS) patients undergoing intravenous thrombolysis (IVT). Methods: We defined a modified Rankin Scale (mRS) score of 3–6 at 90 days as an unfavorable outcome. Logistic regression analysis was performed to find out whether mean platelet volume (MPV), platelet distribution width (PDW), MPV/platelet count (PC) ratio and PDW/PC ratio were associated with poor prognosis. A Spearman correlation test was carried out to assess the relationship between variables. Results : Overall, 183 patients were included in this study. Multivariate logistic regression analysis revealed that MPV (adjusted odds ratio [OR] 1.52, 95% confidence interval [CI]: 1.01–2.29, p  = 0.044) and PDW-sd (adjusted OR 1.30, 95% CI: 1.06–1.59, p  = 0.011) were independent predictors of the poor outcome. There was a trend of incremental OR when compared higher tertile of MPV with lower ones (second tertile, adjusted OR 2.52, 95% CI：1.02–6.21, p  = 0.045； third tertile, adjusted OR 2.61, 95% CI: 1.12–6.09, p  = 0.027). Besides, we found a significant positive correlation between MPV and PDW-sd (or =0.874, p  < 0.001). Conclusion: MPV and PDW-sd were independent predictors for 90-day outcomes in stroke patients receiving thrombolysis.